Low frequency of the TIRAP S180L polymorphism in Africa, and its potential role in malaria, sepsis, and leprosy - Oskam Linda; Bienzle Ulrich; Bedu-Addo George; Alpsoy Erkan; Schuring Ron P; Kumpf Oliver; Hamann Lutz; Mockenhaupt Frank P; Schumann Ralf R (BMC, 2009)
Abstract Background The Toll-like receptors (TLRs) mediate innate immunity to various pathogens. A mutation (S180L) in the TLR downstream signal transducer TIRAP has recently been reported to be common in Europeans and Africans and to roughly half the risks of heterogeneous infectious diseases including malaria, tuberculosis, bacteremia, and invasive pneumococal disease in heterozygous mutation carriers. Methods We assessed the TIRAP S180L variant by melting curve and RFLP analysis in 1095 delivering women from malaria-endemic Ghana, as well as in a further 1114 individuals participating in case control studies on sepsis and leprosy in Germany, Turkey and Bangladesh. Results In Ghana, the TIRAP S180L polymorphism was virtually absent. In contrast, the mutation was observed among 26.6%, 32.9% and 12% of German, Bangladesh and Turkish controls, respectively. No significant association of the heterozygous genotype with sepsis or leprosy was observed. Remarkably, homozygous TIRAP 180L tend to increase the risk of sepsis in the German study (P = 0.04). Conclusion A broad protective effect of TIRAP S180L against infectious diseases per se is not discernible.